Brief Acceptance Commitment Therapy (B-ACT) Kelompok untuk Menurunkan Gejala Stres Kerja pada Pekerja Sosial - Putri Ayu Widyautami; Yudiana Ratnasari (JIP (Jurnal Intervensi Psikologi), 2021)
There are several sources of stress that social workers probably have, which are heavy workload, conflict in superior-subordinate relationships and family problems. The main purpose of this study was to see the effect of group based brief acceptance commitment therapy (B-ACT) in reducing work stress. The design of study used a pretest-posttest one group design.  The subjects involved in this study were seven workers at a nursing home. The data were obtained through interviews, observation, and questionnaires. Statistical analysis using Wilcoxon Signed-Rank Test indicated that B-ACT is not significantly effective in reducing work stress. However, a trend of positive improvement was observed, indicating the potential benefit of B-ACT for reducing work stress in social workers. Limitations of this study are explained in the discussion section.